THE DEVELOPMENT OF HOTS-BASED FINANCIAL MATHEMATICS QUESTION TO SUPPORT STUDETS’ MATHEMATICAL COMMUNICATION SKILL - Sahrul Ramadhan; Elly Arliani; Mayang Purbaningrum; Nur Lailatul Azizah (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Communication skills and high-order thinking skills or HOTS need to be honed in this era, so the aim of this research is to develop financial mathematics HOTS questions to support the mathematical communication skills of grade 11 Vocational High School students. The research method used is development research with a formative research type model. The subjects of this study were 3 grade 11 SMK Negeri in Yogyakarta. The research instrument uses tests and interview guidelines. Data collection techniques using documentation, walkthroughs, tests, and interviews. Data analysis techniques using descriptive techniques. The research results obtained were 15 HOTS questions of mathematical communication on financial mathematics material. The resulting questions have very valid criteria with a validity level of more than 0.8. The questions have a reliability coefficient of more than 0.6 so the questions are very reliable. The questions have differentiating power in the good category. The difficulty level of the questions has 2 categories, namely medium and easy. The distractor on the resulting problem works well. The average test result is in the very good category with a value of 73.13. Based on this research, it is hoped that there will be follow-up in compiling questions for mathematical communication skills in other materials.Kemampuan komunikasi dan kemampuan berpikir tingkat tinggi perlu diasah di era ini, sehingga tujuan penelitian ini yaitu mengembangkan soal HOTS matematika keuangan untuk menunjang kemampuan komunikasi matematis siswa SMK kelas 11. Metode penelitian yang digunakan yaitu penelitian pengembangan dengan model tipe formative research. Subjek penelitian ini 3 kelas 11 SMK Negeri in Yogyakarta. Instrumen penelitian menggunakan tes dan pedoman wawancara. Teknik pengumpulan data menggunakan dokumentasi, walkthrough, tes dan wawancara. Teknik analisis data menggunakan Teknik deskriptif. Hasil penelitian yang diperoleh yaitu 15 Soal HOTS komunikasi matematis pada materi matematika keuangan. Soal yang dihasilkan memiliki kriteria sangat valid dengan tingkat validitas lebih dari 0,8. Soal memiliki hasil koefisien reliabilitas lebih dari 0.6 sehingga soal sangat reliabel. Soal memiliki daya pembeda pada kategori baik. Tingkat kesulitan soal memiliki 2 kategori yaitu sedang dan mudah. Distraktor pada soal yang dihasilkan berfungsi dengan baik. Rata-rata hasil tes pada kategori sangat baik dengan nilai 73,13. Berdasarkan penelitian ini, diharapkan ada tindak lanjut dalam menyusun soal untuk kemampuan komunikasi matematis pada materi lainnya.